'Uthmân dan Fodio et la question du pouvoir en pays haoussa - Thomas Fillitz (Université de Provence, 2000)
In this contribution, the jihâd by'Uthmân dan Fodio will be considered according to the following aspects : on the one hand will be analised the foundations of his power, his time of itinerant preacher, as well as the accentuation of the conflict with the Hausa kings, and his argument to legitimize the Jihâd. On the other hand will be mentioned the concepts which influenced the shaykh and the role of his brother 'Abdullahi, the chief ideologue on his side. However, the major argument is that even iftheJihâd started by some kind of accident, it was nevertheless inevitable because of the concepts of the shaykh.